ANALYSIS OF WORK OF ARABLE AGGREGATE WITH THE TRACTOR OF MTZ-80 AT THE DIFFERENTIAL AND BLOCKED INTERWHEELED DRIVE - Лихвенко, С. П.; Харак, Р. М. (Scientific Progress & Innovations, 2013)
The results of experimental research of work of arable aggregate are presented in composition of the tractor of МТZ-80 and hinge-plate plough on sandy-loam soil at the differential and blocked interwheeled drive of back bridge. It is set as a result of analysis of the obtained data that at the blocked drive tangent tractive of tractor force increases in limits from 3, 99 to 21, and 5 % as compared to a differential drive. The increase of tangent force takes place due to the increase of twisting moment on a right wheel that is in a furrow. Additional tractive force is used for overcoming of increasing force of resistance to motion of aggregate. The blocked interwheeled drive results in worsening of dirigibility of tractor and increase of expense of fuel on the average on 12 %. For maintenance of rectilineal motion of aggregate it is necessary to retain the forewheels of tractor turned to the right, thus, at the blocked drive the corner of turn of wheels increases.